TOD indeks based on factor analysis for rail stations and their surrounding in Jakarta Metropolitan Region - Kridarso, Etty Retnowati; Iskandar, Julindiani; Purnomo, Agus Budi (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
In the Jakarta Metropolitan Region (JMR), railroads have existed since 1872, when the city was still known as Batavia and was ruled by the Dutch. When JMR implemented Transit Oriented Development (TOD) at the start of the twenty-first century, train stations and the surrounding area started to be valued as premium real estate. This study created a TOD index to assess the stations' and their surroundings' conditions regarding TOD characteristics. A TOD index based on Factor Analysis (FA) was computed for each of the 122 railway stations and the areas surrounding them in JMR using twenty-six TOD variables, which were based on the eight components of TOD established by IDTP. The results of this study present the TOD index introduced is comparatively similar to the index calculated by other researchers. Furthermore, we may assess train stations and their environs and provide recommendations for how to make them better as TODs by classifying the stations according to the TOD index.